CLIMATE CHANGE VARIABILITY AND ASSOCIATED HEALTH EFFECTS AMONG FARMING HOUSEHOLDS IN ONDO STATE, NIGERIA - AMINU, FOLASADE OLUREMI; H L, LADAPO; C, AKHIGHE-AHONKHAI E; M O, DAVID (Innovare Journal of Agricultural Sciences, 2021)
Objectives: The study examined climate change variability and associated health effects among farming households in Ondo State, Nigeria. It specifically described the socioeconomic characteristics of the farming households, identified the health issues experienced as a result of climate change, and analyzed the determinants of health effect of climate change and other socioeconomic variables among farming households in the study area. Methods: One hundred and twenty respondents selected through multistage sampling technique were used for the study. Data were collected with the aid of questionnaire and analyzed using descriptive and logit regression model. Results: Majority (92.9%) of the respondents were male, married (82.1%) with a mean household size of six people and a mean age of 49 years. Headache (95.5%), dizziness (95%), malaria (92%), body weakness (91.1%), cough (81.3%), typhoid fever (67.9%), skin rashes (58%), and rheumatic pain (48.2%) were the major health problems experienced by the farming households as a result of climate change in the study area. The significant variables determining the health effects of climate change among farming households in the study area were temperature (p<0.01), relative humidity (p<0.01), rainfall (p<0.01), sunshine (p<0.01), pressure (p<0.10), sex (p<0.10), marital status (p<0.01), household size (p<0.10), farming experience (p<0.01), and income (p<0.05). Conclusion: The health and well-being of the farming households were compromised by the vagaries in climatic condition in the study area. Hence, agricultural extension workers should be empowered to accommodate health education and preparedness measures that take into account, differences in the level of exposure, perceptivity, and acclimation capacity of different households may help to alleviate health effects of climate change on farming households in the study area.